(untitled) (Herald of the National Children’s Medical Center, 2024)
Ovarian apoplexy is a disease of puberty girls. It occupies the third place in the structure of all acute gynecological diseases, accounting for 17%. Among the causes of intra-abdominal bleeding, apoplexy accounts for 0.5- 2.5%.